Efficacy of long‐term treatment with efinaconazole 10% solution in patients with onychomycosis, including severe cases: A multicenter, single‐arm study. Issue 8 (17th June 2019) - Iozumi, Ken; Abe, Masatoshi; Ito, Yoshiko; Uesugi, Takashi; Onoduka, Takashi; Kato, Ichiro; Kato, Fumihiro; Kodama, Kazuo; Takahashi, Hidetoshi; Takeda, Osamu; Tomizawa, Koki; Nomiyama, Tomoko; et al.
Abstract: We evaluated the efficacy of efinaconazole 10% topical solution in long‐term use, for up to 72 weeks, for onychomycosis, including severe cases. Among 605 participants, 219 patients diagnosed as having onychomycosis were evaluated for the efficacy of efinaconazole. The treatment success rate (<10% clinical involvement of the target toenail) at the final assessment time point was 56.6%, the complete cure rate was 31.1% and the mycological cure rate was 61.6%, all of which increased over time, demonstrating that continuous application contributed to the improvement of cure rate. Even in severe cases, reduction of the affected nail area was observed, showing the potential efficacy of the treatment. Responses to a quality of life questionnaire among patients with onychomycosis, OnyCOE‐t, suggested that efinaconazole treatment improved the patients' quality of life. The incidence of adverse drug reaction in the patients eligible for the assessment was 6.3%, and this developed only in the administration site in all cases. No systemic adverse event was observed. In addition, no increase in the incidence of adverse drug reaction due to long‐term use was found. Efinaconazole therapy was proved to exhibit excellent balance between efficacy and safety, and thus may serve as a useful treatment option for onychomycosis.